Malaysian code of corporate governance and tax compliance: evidence from Malaysia / Mohd Taufik Mohd Suffian ... [et al.] - Mohd Suffian, Mohd Taufik; Shamsudin, Siti Marlia; Mohd Sanusi, Zuraidah; Hermawan, Ancella Anitawati (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2017)
In many countries, most of the government relies heavily on tax revenue to finance the government expenditures. In Malaysia, 78.8% of the source of revenue is from tax revenue and mainly contributed by the corporate income tax. The past literature has documented that good corporate governance could increase the firm's performances as well as tax compliance. Malaysia has published its own code of corporate governance in March 2000 and was revised in 2007, 2011 and 2012. Recently, in April 2016, the Security Commission released the recommended MCCG 2016. Thus, judging from the importance of maintaining tax collection, this paper aims to examine the importance of corporate governance in ensuring tax compliance among public listed companies in Malaysia. This study finds that corporate governance does influence tax compliance and multiple directorships is the most significant in influencing tax compliance.